2015
DOI: 10.1186/s12910-015-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a data linkage training workshop for research ethics committees

Abstract: BackgroundIn Australia research projects proposing the use of linked data require approval by a Human Research Ethics Committee (HREC). A sound evaluation of the ethical issues involved requires understanding of the basic mechanics of data linkage, the associated benefits and risks, and the legal context in which it occurs. The rapidly increasing number of research projects utilising linked data in Australia has led to an urgent need for enhanced capacity of HRECs to review research applications involving this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This unmet need reflects researchers' and HREC members' perceived difficulty in considering the ethical implications of SM-based research, their limited confidence and knowledge of ethical issues in this context, and the increasing presence of SM as a research tool. Specialized training workshops can build HREC members' confidence, knowledge, and ethical expertise in other contexts (Tan, Flack, Bear, & Allen, 2015). We therefore recommend that research institutions and ethics committees develop and offer practical training on SM research ethics, and encourage both researchers and HREC members to participate.…”
Section: Educational Implicationsmentioning
confidence: 99%
“…This unmet need reflects researchers' and HREC members' perceived difficulty in considering the ethical implications of SM-based research, their limited confidence and knowledge of ethical issues in this context, and the increasing presence of SM as a research tool. Specialized training workshops can build HREC members' confidence, knowledge, and ethical expertise in other contexts (Tan, Flack, Bear, & Allen, 2015). We therefore recommend that research institutions and ethics committees develop and offer practical training on SM research ethics, and encourage both researchers and HREC members to participate.…”
Section: Educational Implicationsmentioning
confidence: 99%
“…This is compounded by the fact that HREC personnel lack understanding of multijurisdictional privacy implications and the processes of data linkage itself. A national scoping study in 2011 conducted by the PHRN identified that 87% of staff requested more training to equip themselves with the necessary skills . The PHRN offers training modules to improve understanding of the processes in data linkage for HREC, but unfortunately these remain optional.…”
Section: Challengesmentioning
confidence: 99%
“…In the early years of the PHRN it was recognised that the establishment of data centres in all jurisdictions would require human research ethics committees (HRECs) in all jurisdictions to understand data linkage and the ethical issues that arise from the use of linked data, particularly without consent. The PHRN developed a training workshop for HRECs which was run across the country [12].…”
Section: Consent Modelmentioning
confidence: 99%